"From One Shore to the Other": Other Revolutions in the Interstices of the Revolution: An Interview with Imed Soltani and Federica Sossi. Issue 3 (26th December 2017) - Tazzioli, Martina
Abstract: This interview with Imed Soltani and Federica Sossi focuses on the campaign of the families of the missing Tunisian migrants, "From One Shore to the Other: Lives that Matter". The campaign started in 2011 to demand that Italian and Tunisian institutions be held accountable for the disappearance of young Tunisian migrants who crossed the Mediterranean to Italy. The campaign brought together the families of Tunisian migrants and the Italian feminist collective "Le Venticinqueundici" as part of a migration struggle that involves the entire region but is rarely taken up as a cross‐shore militant campaign. The conversation between Soltani and Sossi illustrates the strengths of the campaign and the difficulties that arose in running it across shores, and offers a theoretical reflection on the notion of political recognition in an effort to decolonise the gaze on what counts as political subjectivity and political struggle.